Perencanaan Dinding Penahan Tanah pada Ruas Jalan Dr. J. Leimena. Hative Besar Kota Ambon: The Planning of Retaining Wall on the road of Dr. J. Leimena Hative Besar in Ambon City - Tuasuun, Fanny; Maitimu, Anthoneta; Latar, Sjafrudin (LITERA: Jurnal Ilmiah Mutidisiplin, 2024)
The road of Dr. J. Leimena, which is in Hative Besar Village, Ambon City, is one of the provincial roads affected by landslides caused by high intensity rain and strong winds that hit Ambon City, which caused damage to the retaining walls and also caused damage to Several buildings belonging to residents are located around the retaining wall, so repairs and re-planning of the damaged retaining wall are needed. The design of this retaining wall uses a gravity type wall and uses theory and empirical formulas according to Rankine to calculate active earth pressure and passive earth pressure on the retaining wall as well as terzaghi regarding the bearing capacity of the soil. The results of planning the dimensions of a retaining wall using a gravity type retaining wall with a height (H) = 5 m, bottom width (B) = 3.5 m, top width (T) = 0.8 m and Df = 0.83 m. The safety factor obtained from retaining wall planning is that the wall is stable against shear forces with a value of 2.6 > 1.5 (safe) and the wall is stable against overturning forces with a value of 2.6 > 1.5 (safe).